Alfa-Amilase em rações para frangos de corte com valorização energética - Bruch, Claudia Aloisa (2023)
This study aimed to evaluate two inclusions of exogenous alpha-amylase in diets with metabolizable energy (ME) enhancement on growth performance, carcass and cuts yield, serum biochemical parameters and intestinal health indicators of broiler chickens. A total of 640 male broilers (Cobb 500 lineage and 47.09 ± 0.78 g of body weight) were distributed in 4 treatments of 8 repetitions and 20 birds per experimental unit. The treatments consisted of a positive control diet (PC), negative control (100 kcal ME kg-1 enhancement) (CN), CN plus supplementation of 100 g of exogenous alphaamylase ton-1 and CN plus supplementation of 200 g of exogenous alpha-amylase ton-1. The addition of amylase improved performance parameters and feed conversion in birds, especially in the final growth phase. No variation was observed in carcass and cuts yield, and relative weight of liver, pancreas and abdominal fat with the addition of alpha-amylase. Birds fed a diet containing alpha-amylase at 200 g ton-1 showed greater crypt depth, and the villus height was similar to the control diets in the duodenum segment. Serum biochemical parameters were not influenced by the use of alpha-amylase. The birds that had the addition of 200 g ton-1 alpha-amylase had higher concentrations of acetic and butyric acid in the cecal content. These results suggest that alpha-amylase improves the growth performance and intestinal health of chickens on ME-reduced diets, making this exogenous enzyme a promising alternative in broiler chicken production.